(untitled) (Bangladesh Journal of Agricultural Research, 2023)
Thirty-seven genotypes of Lilium were collected and evaluated under Lilium shade at floriculture Division, Horticulture Research Centre, Bangladesh Agricultural Research Institute, Gazipur during 2017-21 to characterize different species of Lilium available in Bangladesh and collected from abroad. Notable variations in different qualitative and quantitative parameters were observed among the 37 genotypes under study. Among them, 31 genotypes were found suitable for cut flowers and six (06) suitable for pot culture. The longest stalk and rachis (94.3 cm and 36.0 cm, respectively) were produced by the genotype Lil-036. The maximum number of florets per stick (10.5) was produced by BARI Lilium-1. The maximum vase life was observed in Lil-007 and BARI Lilium-2 (11.0 days), whereas the minimum in Lil-022 and Lil-026 (5.0 days). The heaviest and the largest bulbs were produced by the genotype Lil-036 (72.4 g) and (6.6 cm) respectively. Considering the length of stalk and rachis, number of florets per stick, duration of vase life, average bulb weight, the genotypes, Lil-018, Lil-021, Lil-034, Lil-035 and Lil-036 were selected for further evaluation. Bangladesh J. Agril. Res. 47(1): 39-50, March 2022